PENTAHELIX ANALYSIS DALAM UPAYA MITIGASI BENCANA DI DESA SELOK ANYAR KECAMATAN PASIRIAN KABUPATEN LUMAJANG - Achmad Fathoni; Kalvin Edo Wahyudi (Jurnal Ilmu Sosial dan Ilmu Politik)
Indonesia is a country that has the potential for major disasters. This is because Indonesia is between 3 active plates of the world: the Eurasian, Indo-Australian, and Pacific. Indonesia is also located between 2 major world oceans, namely the Indian and Pacific Oceans. This poses the threat of natural disasters in the territory of Indonesia, especially earthquakes, erupting mountains, tsunamis, and other disasters caused by geological activities. This requires the government and the community to be aware of the potential disasters around it. This research was conducted because researchers found that villages that have been trained and have knowledge in dealing with potential disasters and won awards showed that the community still does not understand how to mitigate disasters around them. This research was conducted because researchers found that villages that have been trained and have knowledge in dealing with potential disasters and won awards showed that the community still does not understand how to mitigate disasters around them. This research was conducted to determine the role of 5 parties in the pentahelix theory expressed by Sudiana, namely the Government, Academics, Business People, Media, and the Community Community. Research Methods used in this study used qualitative methods with descriptive purposes with data collection techniques using interviews, observations, and documentation. The results of this study show that disaster mitigation efforts carried out by the pentahelix component in Selok Anyar Village, Pasirian District, Lumajang Regency, East Java, have been running.